Consumer's Buying Behaviour of Motorcycles in Janakpurdham (Journal of Management, 2020)
The paper states the review of the factors that influence consumer buying behaviour of motorcycles in Janakpurdham. The focus of the article is in the area of consumer behaviour that plays a vital role in making decisions to purchase any product. The main objective of this study is to examine the factors that influence buying behaviour of consumers to purchase motorcycles. In this study, the questionnaire method is used to collect data. The study has been done by non-probable convenient sampling method. The main finding of this study is that the male folk play a dominant role in influencing the purchase of motorcycles. Servicemen prefer motorcycles in comparison of professionals, businessmen and others. Income of consumer plays an important role in the consumer buying decision of motorcycles. Price is the most important factor that influences consumer buying behaviour followed by quality. Also promotion plays a major role in influencing the consumer buying behaviour. This study is important to understand the buying behaviour of consumers.